A composite current collector and preparation method thereof
By introducing ultraviolet light to the composite fluid collecting, and using purple light to decompose the gel layer, the problem of difficult metal recovery in the composite fluid collecting is solved, and an efficient and environmentally friendly metal recovery effect is achieved.
Patent Information
- Application Number
- CN202411886096.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
It is difficult to efficiently recover metals in existing composite fluids, and traditional recycling processes have problems of low purity, complex process and environmental pollution.
The ultraviolet degradable gel layer is introduced between the base film of the composite fluid collection and the metal layer, and the gel layer is decomposed by ultraviolet light irradiation, reducing its adhesion force with the metal layer, thereby achieving separation and recovery of the metal layer.
It realizes efficient recycling of metal layers in composite liquid collection, is simple to operate and low cost, avoids environmental pollution caused by chemical recycling, and is suitable for large-scale recycling.
Smart Images

Figure CN119340400B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of current collectors, and in particular to a composite current collector and a preparation method thereof. Background Art
[0002] The existing composite current collector is a "sandwich" structure, with a polymer layer (such as PET, PP or PI) as the inner layer and metal conductive layers (such as Al or Cu) on both sides. In the current industrial mass-produced composite current collectors, composite copper foil often uses polypropylene (OPP) with a thickness of 4.5 μm as the substrate, and a 50 nm copper layer is first plated on both sides of the substrate by magnetron sputtering, and then the copper layer is thickened to about 1 μm by water electroplating. Composite aluminum foil usually uses polyethylene terephthalate (PET) with a thickness of 6 μm as the substrate, and then a 1 μm aluminum layer is plated on both sides of the substrate by evaporation.
[0003] With the maturity of battery recycling technology, the metals in the composite current collector are also expected to be recycled for secondary use. At present, there are three main ways to recycle metals in composite current collectors: one is the traditional powdering process, which is easy to mix some organic matter (polymer in the substrate) into the black powder (metal), which is easy to cause the recycled metal to have low purity; the second is the traditional pyrometallurgical process. For composite aluminum foil, the PET material in the substrate has the characteristics of high temperature resistance and flame retardancy. The traditional pyrometallurgical process cannot volatilize the PET material; the third is the wet process, which often uses alkaline solution, but the alkaline solution will also react with PET. This reaction process makes the PET molecule change from polyester to polyacid, and a large amount of water molecules are produced as by-products, which may increase the difficulty of the recycling process. At present, the chemical separation of PET can be achieved by dissolving it with other organic solvents or using chain extenders to form polymers, but at present, the operation of these two processes is relatively complicated and costly. Therefore, the current recycling of composite current collectors mainly separates the coating and the film through chemical / physical methods. No matter which one is used, it has great difficulties in terms of process, recycling cost and environmental pollution. Summary of the invention
[0004] In order to solve the problem that metals in existing composite current collectors are difficult to recycle, the present invention provides a composite current collector and a preparation method thereof.
[0005] According to a first aspect of the present invention, a composite current collector is provided. The composite current collector includes a base film and an ultraviolet light degradable gel layer and a metal layer sequentially disposed on at least one surface of the base film.
[0006] The composite current collector provided by the present invention adds an ultraviolet light degradable gel layer as a connecting layer between the base film and the metal layer. On the one hand, it can improve the bonding strength between the gel layer and the base film, and between the base films. On the other hand, it is convenient to recycle the metal layer in the composite current collector. The ultraviolet light degradable gel layer will undergo fission and decomposition under ultraviolet light irradiation, and its structure will change, resulting in a decrease in its viscosity. The bonding force between the gel layer and the metal layer is reduced, so that the base film and the metal layer can be separated, thereby achieving the purpose of recycling the metal layer in the composite current collector. The recycling operation is simple, the cost is low, and large-scale recycling can be achieved. At the same time, the environmental pollution problem caused by chemical recovery of the metal layer is avoided.
[0007] Preferably, the UV-degradable gel layer comprises at least one of nitrobenzene compounds, polyacrylate compounds, and methacrylated gelatin.
[0008] Preferably, the nitrobenzene compound includes L-2-nitrophenylalanine; and the polyacrylate compound includes polymethacrylate.
[0009] Nitrobenzene compounds, polyacrylate compounds and methacrylated gelatin all have good viscosity and can be decomposed under ultraviolet light. One or more of the nitrobenzene compounds, polyacrylate compounds and methacrylated gelatin are formed into a gel layer and introduced between the base film and the metal layer of the composite current collector. The base film and the metal layer are connected through the gel layer, which can not only improve the adhesion between the gel layer and the base film and the metal layer, but also make the gel layer in the composite current collector decompose under ultraviolet light, thereby achieving viscosity reduction between the base film and the metal layer, and facilitating the recovery of the metal layer in the composite current collector.
[0010] Preferably, the UV-degradable gel layer comprises polymethacrylate.
[0011] Polymethacrylate can be decomposed under ultraviolet light with a wavelength of 260 nm. Compared with L-2-nitrophenylalanine (which can be decomposed under ultraviolet light with a wavelength of 300 nm), methacrylated gelatin (which can be decomposed under ultraviolet light with a wavelength of 320 nm) and other polyacrylate compounds, this scheme uses polymethacrylate as a component of the ultraviolet light degradable gel layer. On the one hand, the adhesion between the gel layer and the base film and the metal layer is further improved. On the other hand, the minimum ultraviolet light wavelength for the degradation of polymethacrylate is shorter, and under the irradiation of ultraviolet light of the same wavelength, polymethacrylate is more easily decomposed, making it easier to recover the metal layer in the composite collector.
[0012] Preferably, the moisture content of the UV-degradable gel layer is 0.05-1 wt %.
[0013] By controlling the moisture content of the UV-degradable gel layer in the composite current collector within the above range, it is beneficial to improve the mechanical properties of the gel layer, thereby giving the composite current collector good mechanical properties. If the moisture content of the UV-degradable gel layer disposed between the base film and the metal layer in the composite current collector is too high, it will affect the electrochemical properties of the composite current collector; if the moisture content of the UV-degradable gel layer disposed between the base film and the metal layer in the composite current collector is too low, it will make it difficult for the gel layer to spread evenly on the surface of the base film, thereby affecting the mechanical properties of the composite current collector.
[0014] Preferably, the thickness of the UV-degradable gel layer is 0.5-1 μm.
[0015] Controlling the thickness of the UV-degradable gel layer in the composite current collector within the above range can ensure the viscosity of the gel layer and avoid the displacement of the metal layer due to overflow of the gel layer. If the thickness of the gel layer is too thin, it is easy to cause the viscosity to be too low, thereby reducing the bonding force between the gel layer and the metal layer; if the thickness of the gel layer is too thick, it is easy to cause overflow of the gel layer, resulting in the displacement of the metal layer, thereby deteriorating the performance of the composite current collector.
[0016] Preferably, the thickness of the base film is 6-8 μm.
[0017] Controlling the thickness of the base film of the composite current collector within the above range can not only improve the energy density of the composite current collector, but also improve the mechanical strength of the composite current collector and reduce the risk of fracture. If the thickness of the base film in the composite current collector is too thin, the base film is prone to fracture during the preparation of the composite current collector or the mechanical strength of the composite current collector obtained is reduced; if the thickness of the base film in the composite current collector is too thick, the energy density of the battery using the composite current collector will be reduced.
[0018] Preferably, the thickness of the metal layer is 1-2 μm.
[0019] Controlling the thickness of the metal layer in the composite current collector within the above range can not only improve the energy density of the battery using the composite current collector, but also keep the sheet resistance of the metal layer within an appropriate range, thereby reducing the resistance of the battery using the composite current collector. If the thickness of the metal layer in the composite current collector is too thin, the sheet resistance of the metal layer of the composite current collector will be too high, thereby increasing the resistance of the battery using the composite current collector; if the thickness of the metal layer in the composite current collector is too thick, the energy density of the battery using the composite current collector will be reduced.
[0020] According to a second aspect of the present invention, there is provided a method for preparing a composite current collector, comprising the following steps:
[0021] S1. preparing a gel solution using UV-degradable gel powder and a solvent;
[0022] S2. Applying the glue solution on at least one surface of the base film to form a UV-degradable gel layer, and coating a metal layer on the surface of the UV-degradable gel layer using a vacuum evaporation process to obtain a composite current collector.
[0023] A UV-degradable gel layer is formed by coating a glue solution containing UV-degradable gel on the surface of a base film, and a metal layer is plated on the surface of the gel layer using a vacuum evaporation process. The gel layer of the composite current collector prepared by the above method has a high adhesion to the base film and the metal layer, and the purpose of recovering the metal layer in the composite current collector can be achieved by simply using UV light irradiation.
[0024] Preferably, in the vacuum evaporation process, the vacuum degree is controlled to be 8~15 Pa.
[0025] Preferably, in the vacuum evaporation process, the evaporation distance is controlled to be 10-20 cm.
[0026] In the process of plating a metal layer on the surface of a UV-degradable gel layer using a vacuum evaporation process, controlling the vacuum degree and / or the evaporation distance within the above-mentioned range can improve the light transmittance of the metal layer in the final composite current collector. When the composite current collector is irradiated with ultraviolet light, the higher the light transmittance of the metal layer, the more ultraviolet light is absorbed by the gel layer, making it easier to degrade the gel layer, and the viscosity reduction effect is more obvious. The bonding force between the metal layer and the base film is significantly reduced, thereby greatly improving the recovery efficiency of the metal layer in the composite current collector. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the structure of the composite current collector provided by the present invention.
[0028] The reference numerals in the accompanying drawings are: 1 base film, 2 UV-degradable gel layer, 3 metal layer. DETAILED DESCRIPTION
[0029] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A composite current collector having a structure as Figure 1As shown, the composite current collector includes a base film 1 and an ultraviolet light degradable gel layer 2 and a metal layer 3 sequentially arranged on two surfaces of the base film 1, wherein the base film 1 is made of PET (polyethylene terephthalate) and the metal layer 3 is an aluminum layer;
[0032] The composite current collector provided in this embodiment is prepared by the following steps:
[0033] S1. The methacrylic gelatin solid powder is dissolved in water and dispersed evenly to prepare a glue solution;
[0034] S2. The above-mentioned glue is coated on both surfaces of a base film 1 with a thickness of 7 μm to form a UV-degradable gel layer 2, and is dried at 50°C until the moisture content of the UV-degradable gel layer 2 is between 0.05 and 1 wt%, to obtain a semi-finished product, wherein the thickness of the UV-degradable gel layer 2 is 0.8 μm, and then the semi-finished product is fixed to a winding trolley, wherein the semi-finished product end is at 120 N and the winding end is at 100 N. After the winding trolley enters the evaporation chamber, it is evacuated to 15 Pa, and the distance from the evaporation boat to the surface of the semi-finished product is adjusted to 20 cm. The winding trolley is turned on and the speed of the winding trolley is controlled to be 280~300 m / min. At the same time, the evaporation boat is heated and the aluminum wire is fed at a speed of 300~350 mm / min. The vacuum degree is controlled at 15 Pa, and then the vacuum is broken and a layer of aluminum layer with a thickness of 1.5 μm is plated on the surface of the semi-finished product as a metal layer 3 in the same manner to obtain a composite current collector.
[0035] Example 2
[0036] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the composite current collector, polymethacrylate solid powder is used to replace methacrylated gelatin solid powder. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0037] Example 3
[0038] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the composite current collector, L-2-nitrophenylalanine solid powder is used to replace the methacrylated gelatin solid powder. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0039] Example 4
[0040] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the composite current collector, chitosan-polycrotonic acid hydrogel powder is used to replace the methacrylated gelatin solid powder. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0041] Example 5
[0042] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the composite current collector, polyvinyl alcohol hydrogel powder is used to replace methacrylated gelatin solid powder. Except for the above difference, the materials, formula ratio and preparation operation used in this embodiment are strictly consistent with those in the embodiment 1.
[0043] Example 6
[0044] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step S2 of the composite current collector, the distance between the evaporation boat and the surface of the semi-finished product is adjusted to 10 cm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0045] Example 7
[0046] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step S2 of the composite current collector, the distance between the evaporation boat and the surface of the semi-finished product is adjusted to 15 cm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0047] Example 8
[0048] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is: (1) in the preparation step S2 of the composite current collector, the winding trolley is evacuated to 8 Pa after entering the evaporation chamber, and the vacuum degree is controlled at 8 Pa during the feeding of the aluminum wire; (2) in the preparation step S2 of the composite current collector, the distance between the evaporation boat and the surface of the semi-finished product is adjusted to 10 cm. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0049] Example 9
[0050] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is: (1) in the preparation step S2 of the composite current collector, the winding trolley is evacuated to 11 Pa after entering the evaporation chamber, and the vacuum degree is controlled at 11 Pa during the feeding of the aluminum wire; (2) in the preparation step S2 of the composite current collector, the distance from the evaporation boat to the surface of the semi-finished product is adjusted to 10 cm. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0051] Example 10
[0052] This embodiment provides a composite current collector, and compared with Embodiment 1, the difference in structure is that in the preparation step S2 of the composite current collector, the winding trolley is evacuated to 5 Pa after entering the evaporation chamber, and the vacuum degree is controlled at 5 Pa during the feeding of the aluminum wire. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Embodiment 1.
[0053] Embodiment 11
[0054] This embodiment provides a composite current collector, and compared with Embodiment 1, the difference in structure is that in the preparation step S2 of the composite current collector, the winding trolley is evacuated to 20 Pa after entering the evaporation chamber, and the vacuum degree is controlled at 20 Pa during the feeding of the aluminum wire. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Embodiment 1.
[0055] Example 12
[0056] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step S2 of the composite current collector, the distance between the evaporation boat and the surface of the semi-finished product is adjusted to 5 cm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0057] Example 13
[0058] This embodiment provides a composite current collector. Compared with the embodiment 1, the difference in structure is that in the preparation step S2 of the composite current collector, the distance between the evaporation boat and the surface of the semi-finished product is adjusted to 25 cm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0059] Comparative Example 1
[0060] This comparative example provides a composite current collector, which is different from Example 1 in that the composite current collector does not contain a UV-degradable gel layer. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0061] Test Case
[0062] 1. Participants
[0063] In this test example, the composite current collectors prepared in Examples 1 to 13 and Comparative Example 1 were used as test objects to conduct relevant performance tests.
[0064] 2. Test content
[0065] (1) Light transmittance
[0066] The composite current collector was cut into a size of 50 mm*50 mm, and the transmittance of the composite current collector was directly measured using an LS117 spectrometer.
[0067] (2) Peel strength
[0068] The composite current collector was cut into test samples with a size of 15 mm×100 mm, and 3M-9080A-15mm tape was attached to a stainless steel plate. The measured sample was evenly attached to the double-sided tape and rolled back and forth twice with a 2 kg standard small roller. Then, 3M-9080A-14mm tape was attached to the surface of the test sample and rolled back and forth twice with a 2 kg standard small roller. The pressed test sample was then placed on a tensile testing machine and stretched at 180° for peeling. The speed was 100 mm / min and the width was set to 14 mm. The peel strength result was taken as the maximum value. The peel strength between the gel layer and the metal layer of the composite current collector was tested before and after ultraviolet light irradiation (ultraviolet light wavelength was 800 nm and irradiation time was 10 min).
[0069] 3. Experimental results
[0070] Table 1 Related performance test results of composite current collector
[0071]
[0072] The relevant performance test results of the composite current collectors provided in Examples 1 to 13 and Comparative Example 1 are shown in Table 1.
[0073] Compared with Comparative Example 1, the composite current collectors provided in Examples 1 to 13 include a base film and a UV-degradable gel layer and a metal layer sequentially arranged on two surfaces of the base film. The test results show that the peel strength between the metal layer and the gel layer of the composite current collector provided in Comparative Example 1 before and after UV irradiation is high and close, which are 1125 N / m and 1203 N / m, respectively. The peel strength between the metal layer and the gel layer of the composite current collectors provided in Examples 1 to 13 before UV irradiation is high, both above 1000 N / m, and the peel strength between the metal layer and the gel layer after UV irradiation is significantly reduced, both above 600 N / m. N / m or less. This is mainly because the composite current collectors provided in Examples 1 to 13 can improve the adhesion between the gel layer and the base film and the metal layer by adding a UV-degradable gel layer as a connecting layer between the base film and the metal layer, so that the composite current collector has a higher peel strength between the metal layer and the gel layer before UV irradiation. After UV irradiation, the gel layer in the composite current collector undergoes fission and decomposition, and its structure changes, resulting in a decrease in its viscosity, thereby reducing the peel strength between the gel layer and the metal layer, thereby achieving separation of the base film and the metal layer, and facilitating the recovery of the metal layer in the composite current collector.
[0074] In Examples 1 to 3, before ultraviolet light irradiation, the peel strengths between the gel layer and the metal layer in the composite current collectors provided in Examples 1 to 3 are relatively close, while after ultraviolet light irradiation, the peel strength between the gel layer and the metal layer in the composite current collector provided in Example 2 is significantly lower than that in Examples 1 and 3. This is mainly because the raw materials for preparing the UV-degradable gel layer in the composite current collectors provided in Examples 1 and 3 are methacrylated gelatin and L-2-nitrophenylalanine, respectively. Compared with methacrylated gelatin and L-2-nitrophenylalanine, the minimum UV wavelength for degradation of the raw material polymethacrylate used in preparing the UV-degradable gel layer in the composite current collector provided in Example 2 is shorter, and under ultraviolet light irradiation of the same wavelength, polymethacrylate is more easily decomposed, so that the peel strength between the gel layer and the metal layer is lower, which is more conducive to the recovery of the metal layer in the composite current collector.
[0075] Compared with Example 1, the raw materials for preparing the UV-degradable gel layer in the composite current collectors provided in Examples 4 and 5 are chitosan-polycrotonic acid hydrogel powder and polyvinyl alcohol hydrogel powder, respectively. The test results show that the peel strength between the gel layer and the metal layer in the composite current collectors provided in Examples 4 and 5 is equivalent to that in Example 1. However, after ultraviolet light irradiation, the peel strength between the gel layer and the metal layer is significantly higher than that in Example 1, resulting in poor recovery effect of the metal layer in the composite current collector.
[0076] Compared with Example 1, in the process of plating a metal layer on the surface of the UV-degradable gel layer by vacuum evaporation process in Examples 10 and 11, the vacuum degree is not within the range of 8 to 15 Pa. In the process of plating a metal layer on the surface of the UV-degradable gel layer by vacuum evaporation process in Examples 12 and 13, the evaporation distance is not within the range of 10 to 20 cm. The test results show that the peel strength between the gel layer and the metal layer in the composite current collectors provided by Examples 10, 11, 12, and 13 is equivalent to that in Example 1, and the transmittance of the composite current collector is lower than that in Example 1. Therefore, after ultraviolet light irradiation, the gel layer absorbs less ultraviolet light than Example 1, which leads to higher peel strength between the gel layer and the metal layer than that in Example 1, and the recovery effect of the metal layer in the composite current collector is slightly worse than that in Example 1.
[0077] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A composite current collector, characterized in that: The composite current collector comprises a base film, and a UV-degradable gel layer and a metal layer sequentially arranged on at least one surface of the base film, wherein the UV-degradable gel layer comprises at least one of a nitrobenzene compound, a polyacrylate compound, and methacrylated gelatin; The composite current collector is prepared by the following steps: S1. preparing a gel solution using UV-degradable gel powder and a solvent; S2. Apply the glue solution on at least one surface of the base film to form a UV-degradable gel layer, and use a vacuum evaporation process to plate a metal layer on the surface of the UV-degradable gel layer to obtain the composite current collector, wherein in the vacuum evaporation process, the vacuum degree is controlled to be 8~15 Pa, and the evaporation distance is 10~20 cm.
2. The composite current collector according to claim 1, characterized in that: The nitrobenzene compound includes L-2-nitrophenylalanine; The polyacrylate compound includes polymethacrylate.
3. The composite current collector according to claim 1, characterized in that: The UV-degradable gel layer includes polymethacrylate.
4. The composite current collector according to claim 1, characterized in that: The moisture content of the UV-degradable gel layer is 0.05-1 wt %.
5. The composite current collector according to claim 1, characterized in that: The thickness of the UV-degradable gel layer is 0.5-1 μm.
6. The composite current collector according to claim 1, characterized in that: The base film has a thickness of 6-8 μm, and / or the metal layer has a thickness of 1-2 μm.
Citation Information
Patent Citations
Composite current collector base membrane, composite current collector and battery cell
CN116706087A
Cited By
Composite current collector and preparation method thereof
CN121011671A